Volume discharge excited by an electron beam in an Ar-SF6 mixture; II; Cascade ionization discharge; Russian Physics Journal; Vol. 21, № 7 - Bychkov Yu. I.; Korolev Yu. D.; Mesyats G. A. Gennady Andreyevich; Khuzeev A. P.; Shemyakin I. A. (1978, 1978)
В фонде НТБ ТПУ отсутствует